2017
DOI: 10.1104/pp.17.00659
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Diterpenoids in Tripterygium Adventitious Root Cultures

Abstract: ORCID IDs: 0000-0003-4828-958X (M.H.); 0000-0001-7934-7987 (N.S.); 0000-0002-4080-8608 (A.N.P.); 0000-0003-4691-8477 (R.J.P.); 0000-0001-6565-9584 (B.M.L.).Adventitious root cultures were developed from Tripterygium regelii, and growth conditions were optimized for the abundant production of diterpenoids, which can be collected directly from the medium. An analysis of publicly available transcriptome data sets collected with T. regelii roots and root cultures indicated the presence of a large gene family (with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 44 publications
(62 reference statements)
1
21
0
2
Order By: Relevance
“…These were found to consist of not only the expected class II diterpene cyclases that produce CPP, termed here TwTPS7v2 and TwTPS9v2, but also the unusual finding of a subsequently acting class I diterpene synthase, TwTPS27v2, which is not from the TPS-e subfamily that typically provides such enzymes in labdane-related diterpenoid biosynthesis (Zi et al, 2014), rather being derived from the phylogenetically distinct TPS-b subfamily instead. While similar biochemical characterization has been very recently reported for both presumably allelic copies of these T. wilfordii diterpene synthases (Hansen et al, 2017a), as well as the orthologs from T. regelii (Inabuy et al, 2017), the data reported here go beyond this to unambiguously demonstrate the role of the characterized enzymes in triptolide biosynthesis. Most critically, in addition to showing subcellular localization of these enzymes to the plastid, where such diterpene biosynthesis occurs in planta, this includes genetic evidence, with RNAi knock-down of these genes leading to reduced triptolide levels.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…These were found to consist of not only the expected class II diterpene cyclases that produce CPP, termed here TwTPS7v2 and TwTPS9v2, but also the unusual finding of a subsequently acting class I diterpene synthase, TwTPS27v2, which is not from the TPS-e subfamily that typically provides such enzymes in labdane-related diterpenoid biosynthesis (Zi et al, 2014), rather being derived from the phylogenetically distinct TPS-b subfamily instead. While similar biochemical characterization has been very recently reported for both presumably allelic copies of these T. wilfordii diterpene synthases (Hansen et al, 2017a), as well as the orthologs from T. regelii (Inabuy et al, 2017), the data reported here go beyond this to unambiguously demonstrate the role of the characterized enzymes in triptolide biosynthesis. Most critically, in addition to showing subcellular localization of these enzymes to the plastid, where such diterpene biosynthesis occurs in planta, this includes genetic evidence, with RNAi knock-down of these genes leading to reduced triptolide levels.…”
Section: Discussionsupporting
confidence: 88%
“…The ability of T. wilfordii suspension cell cultures to produce valuable terpenoids, particularly the abeo ‐abietane tri‐expoxide triptolide, has long been appreciated (Kutney et al ., ). The suspension cell cultures used here constitutively produce 53 ± 3 μg g −1 of triptolide in the suspension cells and 4.0 ± 0.2 mg l −1 in the medium, which is slightly lower than that of recently reported Tripterygium adventitious root cultures (90 ± 80 μg g −1 in the adventitious roots and 4.7 ± 0.9 mg l −1 in the medium; Inabuy et al ., ). Here the utility of these cell cultures for investigation of triptolide biosynthesis was first demonstrated by not only finding that miltiradiene can be detected therein but also that feeding this olefin leads to increased accumulation, as well as the presence of several other plausible biosynthetic intermediates.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, the biosynthetic pathway of celastrol remains unknown. The pharmaceutical potential of triptolide has led many researchers to investigate the biosynthetic pathway of this compound (Forman et al ., ; Hansen et al ., ; Inabuy et al ., ; Su et al ., ), but there have been few reports on the biosynthetic pathway of celastrol.…”
Section: Introductionmentioning
confidence: 98%